Targeting euchromatic histone lysine methyltransferases sensitizes colorectal cancer to histone deacetylase inhibitors: cancer therapy and prevention - Bamberg, Leonhard Valentin; Heigwer, Florian; Wandmacher, Anna Maxi; Singh, Ambika; Betge, Johannes; Rindtorff, Niklas; Werner, Johannes; Josten, Julia; Skabkina, Olga Valerievna; Hinsenkamp, Isabel; Erdmann, Gerrit; Röcken, Christoph; et al. (International journal of cancer, 2022)
Epigenetic dysregulation is an important feature of colorectal cancer (CRC). Combining epigenetic drugs with other antineoplastic agents is a promising treatment strategy for advanced cancers. Here, we exploited the concept of synthetic lethality to identify epigenetic targets that act synergistically with histone deacetylase (HDAC) inhibitors to reduce the growth of CRC. We applied a pooled CRISPR-Cas9 screen using a custom sgRNA library directed against 614 epigenetic regulators and discovered that knockout of the euchromatic histone-lysine N-methyltransferases 1 and 2 (EHMT1/2) strongly enhanced the antiproliferative effect of clinically used HDAC inhibitors. Using tissue microarrays from 1066 CRC samples with different tumor stages, we showed that low EHMT2 protein expression is predominantly found in advanced CRC and associated with poor clinical outcome. Cotargeting of HDAC and EHMT1/2 with specific small molecule inhibitors synergistically reduced proliferation of CRC cell lines. Mechanistically, we used a high-throughput Western blot assay to demonstrate that both inhibitors elicited distinct cellular mechanisms to reduce tumor growth, including cell cycle arrest and modulation of autophagy. On the epigenetic level, the compounds increased H3K9 acetylation and reduced H3K9 dimethylation. Finally, we used a panel of patient-derived CRC organoids to show that HDAC and EHMT1/2 inhibition synergistically reduced tumor viability in advanced models of CRC.